An introduction to virtual sound barriers - Qiu, Xiaojun (Boca Raton : Taylor & Francis, a CRC title, part of the Taylor & Francis imprint, a member of the Taylor & Francis Group, the academic division of T&F Informa, plc, 2019)
A virtual sound barrier is an active noise control system that uses arrays of loudspeakers and microphones to create a useful size of quiet zone and can be used to reduce sound propagation, radiation, or transmission from noise sources or to reduce noise level around people in a noisy environment. This book introduces the history, principle, and design methods of virtual sound barriers first, and then describes recent progress in research on the systems. Two virtual sound barrier systems, i.e., planar virtual sound barrier system and three-dimensional virtual sound barrier system, are discussed including applications, limitations and future direction discussions.
3.4.3 A Hybrid Virtual Sound Barrier near a Surface3.5 Error-Sensing Strategies; 3.5.1 Formulation; 3.5.2 Simulations; 3.5.3 A General Cost Function; 3.6 Virtual Error Sensors; 3.6.1 Formulation; 3.6.2 Simulations; 3.6.3 Remarks; 4: Applications; 4.1 Noise Radiation Control from Power Transformers in a Hemi-Closed Space; 4.2 Sound Transmission Control through an Open Window into a Room; 4.3 Implementation Issues; 5: Summary and Perspectives; 5.1 Summary; 5.2 Perspectives; 5.2.1 Future Research Topics; 5.2.2 Challenges for the Applications; References; Index
OCLC-licensed vendor bibliographic record.
Keywords: Noise barriers -- Mathematical models; Absorption of sound; Soundproofing; TECHNOLOGY / Acoustics & Sound; TECHNOLOGY / Engineering / Civil; TECHNOLOGY / Engineering / Mechanical